Predictive moral sensitivity in nursing students: The roles of empathy and spiritual health - Nayereh Baghcheghi; Hamid Reza Koohestani; Mahmood Karimy; Mohammad Hasan Keshavarzi (Journal of Education and Health Promotion)
BACKGROUND: The evidence indicates a phenomenon of ethical erosion in healthcare students. Variables like empathy and spiritual health might affect moral sensitivity in nursing students. The present study is an attempt to predict the moral sensitivity of nursing students based on empathy and spiritual health. MATERIALS AND METHODS: A cross-sectional and analytical study was carried out at Saveh University of Medical Sciences, Saveh, Iran, in 2023. In total, 110 nursing students were included in the study by census method. Data gathering was done using Ellison and Paloutzian spiritual health inventory, Jefferson’s empathy inventory, and Lutzen’s moral sensitivity scale. The collected data was analyzed using Pearson’s correlation and multiple regression analysis. RESULTS: The mean scores of empathy, spiritual health, and moral sensitivity in nursing students were equal to 99.8 ± 15.25, 81.32 ± 10.01, and 65.09 ± 12.23 respectively. Empathy and spiritual health were positively and significantly related to moral sensitivity (P < 0.01). In total, 31% of variation in moral sensitivity was attributed to empathy and spiritual health. CONCLUSION: Empathy and spiritual health were positively and significantly related to moral sensitivity. Taking into account the role of spiritual health and moral sensitivity in nursing students, enhancing this aspect of health through informing individuals and highlighting the positive aspects and potential effects on physical and mental health and professional performance in return is recommended.